Registration of 'Vision 50' Wheat. Issue 2 (28th March 2019) - Liu, L.; Barnett, M. D.; Griffey, C. A.; Malla, S.; Brooks, W. S.; Seago, J. E.; Fitzgerald, J.; Thomason, W. E.; Rucker, E. G.; Behl, H. D.; Pitman, R. M.; Dunaway, D. W.; et al.
Abstract : 'Vision 50' (Reg. No. CV‐1152, PI 679953), a hard red winter (HRW) wheat ( Triticum aestivum L.) cultivar, was derived from the cross 'Jagalene'/'Provinciale' using a modified bulk breeding method. Vision 50 was tested as VA09HRW‐64 in replicated yield trials in Virginia (2011–2017) and in the USDA‐ARS Uniform Bread Wheat Trials (2012–2017) and released by the Virginia Agricultural Experiment Station in 2016. Vision 50 is a widely adapted, high‐yielding, awned, semidwarf (unknown Rht gene) HRW wheat having mid‐ to late‐season spike emergence, strong straw strength, and resistance or moderate resistance to diseases prevalent in the mid‐Atlantic region. In the Virginia Bread Wheat Elite Test from 2014 to 2017, Vision 50 produced a mean yield of 5067 kg ha −1 that was similar to the highest‐yielding (5757 kg ha −1 ) cultivar Shirley, a soft red winter wheat check. Vision 50 has acceptable end‐use quality on the basis of comparisons with the HRW wheat check cultivar Jagger for wheat protein (11.3 vs. 12.2 g 100 g −1 ), flour yield (72.7 vs. 66.4 g 100 g −1 ), flour water absorption (59.5 vs. 62.3 g 100 g −1 ), dough mixing tolerance (2.7 vs. 3.0), pup‐loaf volume (815 vs. 822 cm 3 ), and crumb grain scores (4.2 vs. 3.8).